2004
DOI: 10.1103/physrevd.70.114029
|View full text |Cite|
|
Sign up to set email alerts
|

General effective action for high-density quark matter

Abstract: We derive a general effective action for quark matter at nonzero temperature and/or nonzero density. For this purpose, we distinguish irrelevant from relevant quark modes, as well as hard from soft gluon modes by introducing two separate cut-offs in momentum space, one for quarks, Λq, and one for gluons, Λg. We exactly integrate out irrelevant quark modes and hard gluon modes in the functional integral representation of the QCD partition function. Depending on the specific choice for Λq and Λg, the resulting e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Since the classical form of (15) has been reproduced by various experiments at different scales, and since the special choice of c 4 allows to approximate very well to this result, it can be concluded that the solution (4) allows also for parameter choices which are also in agreement with current experimental limits and observations. The question to which extend observational data such as dark matter effects can be incorporated in the current solution (in the spirit of [54][55][56][57][58]) will be subject of future studies [59]. The above choice of parameters is most likely not the only one that achieves this goal, but the point is that it shows by construction that physically viable parameter choices are perfectly possible.…”
Section: A Classical-like Choice Of Parametersmentioning
confidence: 99%
“…Since the classical form of (15) has been reproduced by various experiments at different scales, and since the special choice of c 4 allows to approximate very well to this result, it can be concluded that the solution (4) allows also for parameter choices which are also in agreement with current experimental limits and observations. The question to which extend observational data such as dark matter effects can be incorporated in the current solution (in the spirit of [54][55][56][57][58]) will be subject of future studies [59]. The above choice of parameters is most likely not the only one that achieves this goal, but the point is that it shows by construction that physically viable parameter choices are perfectly possible.…”
Section: A Classical-like Choice Of Parametersmentioning
confidence: 99%
“…In most existing studies [10,11,12,12], due the explicit choice of the functional form of k(x), one always had to sacrifice either general covariance (12), or the conservation of the stress energy tensor (13). In contrast to this, we propose to use the identity (14) in order to determine the relation between k and x ν .…”
Section: (B)mentioning
confidence: 99%
“…In several analytical and numerical studies supporting evidence for this kind of scenario has been found [2,3,4,5,6,7,8,9]. In order to test the implications of this approach it has been studied in a large variety of contexts: Cosmology and Astrophysics [10,11,12,13,14,15,16], Brans Dicke theory [17], black holes [18,19,20,21,22], black holes in extra dimensions [23,24,25,26], interactions in extra dimensions [6], modified dispersion relations [27], f(R) gravity [28], deformed special relativity [29], and gravitational collapse [30]. This work contributes to the above studies in three ways:…”
Section: Introductionmentioning
confidence: 99%
“…where ξ is a O(1) parameter that is kept free for the time being. For the sake of completeness, it has to be pointed out that other choices are possible, as for exemple the cutoff k ∼ 1/t proposed in [24,26,28] or the k ∼ 1/a(t) in [29,30], while in [31][32][33] the cutoff dependence was adjusted to fit the energy-momentum conservation of ordinary matter.…”
Section: Renormalization Group Derived Backgroundmentioning
confidence: 99%